A Fourth KLK4 Mutation Is Associated with Enamel Hypomineralisation and Structural Abnormalities - Smith, Claire E. L.; Kirkham, Jennifer; Day, Peter F.; Soldani, Francesca; McDerra, Esther J.; Poulter, James A.; Inglehearn, Christopher F.; Mighell, Alan J.; Brookes, Steven J. (Frontiers in Physiology, 2017)
“Amelogenesis imperfecta” (AI) describes a group of genetic conditions that result in defects in tooth enamel formation. Mutations in many genes are known to cause AI, including the gene encoding the serine protease, kallikrein related peptidase 4 (KLK4), expressed during the maturation stage of amelogenesis. In this study we report the fourth KLK4 mutation to be identified in autosomal recessively-inherited hypomaturation type AI, c.632delT, p.(L211Rfs*37) (NM_004917.4, NP_004908.4). This homozygous variant was identified in five Pakistani AI families and is predicted to result in a transcript with a premature stop codon that escapes nonsense mediated decay. However, the protein may misfold, as three of six disulphide bonds would be disrupted, and may be degraded or non-functional as a result. Primary teeth were obtained from one affected individual. The enamel phenotype was characterised using high-resolution computerised X-ray tomography (CT), scanning electron microscopy (SEM), energy dispersive X-ray spectroscopy (EDX) and microhardness testing (MH). Enamel from the affected individual (referred to as KLK4 enamel) was hypomineralised in comparison with matched control enamel. Furthermore, KLK4 inner enamel was hypomineralised compared with KLK4 outer enamel. SEM showed a clear structural demarcation between KLK4 inner and outer enamel, although enamel structure was similar to control tissue overall. EDX showed that KLK4 inner enamel contained less calcium and phosphorus and more nitrogen than control inner enamel and KLK4 outer enamel. MH testing showed that KLK4 inner enamel was significantly softer than KLK4 outer enamel (p<0.001). However the hardness of control inner enamel was not significantly different to that of control outer enamel. Overall, these findings suggest that the KLK4 c.632delT mutation may be a common cause of autosomal recessive AI in the Pakistani population. The phenotype data obtained mirror findings in the Klk4-/- mouse and suggest that KLK4 is required for the hardening and mineralisation of the inner enamel layer but is less essential for hardening and mineralisation of the outer enamel layer.